2013
DOI: 10.1002/ajmg.a.36060
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary treatment of disability in ehlers–danlos syndrome hypermobility type/hypermobility syndrome: A pilot study using a combination of physical and cognitive‐behavioral therapy on 12 women

Abstract: Ehlers-Danlos Syndrome hypermobility type (EDS-HT) and joint hypermobility syndrome (JHS) are two overlapping heritable connective tissue disorders. Patients with these conditions have many and various complaints; limitations in performing daily activities, reduced muscle strength and proprioception, kinesiophobia, and pain. There is a lack of evidence-based treatment approaches; a few studies have shown effect of physiotherapy. Many authors propose multidisciplinary treatment, but this has neither been descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 36 publications
3
67
0
1
Order By: Relevance
“…However, there are no studies exploring the coping strategies in JHS/hEDS and psychological aspects of pain perception merits more research to develop treatments programs. Some pilot cognitive behavioral therapy (CBT) experiences have been developed and suggested that CBT is valuable in the pain management of JHS/hEDS patients [Bathen et al, ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are no studies exploring the coping strategies in JHS/hEDS and psychological aspects of pain perception merits more research to develop treatments programs. Some pilot cognitive behavioral therapy (CBT) experiences have been developed and suggested that CBT is valuable in the pain management of JHS/hEDS patients [Bathen et al, ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This type of presentation should be considered as a centralized pain state belonging to the spectrum of chronic widespread pain, with additional superimposed musculoskeletal components. Some patients who continue to struggle to cope with their pain may need consideration of a multidisciplinary pain management program [Bathen et al, ].…”
Section: Managementmentioning
confidence: 99%
“…Psychological counseling should focus on accepting and coping with chronic pain and chronic disease. Cognitive behavioral therapy is particular beneficial, if the patient is willing to actively engage in the process [Bathen et al, ]. Distraction, hypnosis, and judicious use of anti‐depressant medication can also help.…”
Section: Managementmentioning
confidence: 99%
“…A predominant myopath- ic category would correlate with AAD symptoms in many non-CTD conditions that exhibit hypotonia/poor muscle development [53] and explain why 6 patients with developmental disabilities had DNA variants of relevance to AAD in Table 2. Less muscle support and protection leading to joint-tissue laxity would explain the established benefits of exercise [54] and physical therapy [55] for EDS. Impact on the various tissue elements shown in Figure 3 adds focus on patient-derived stem cells that could repair multiple mesodermal tissues [56] [57], their gene defects characterized by WES and perhaps corrected by emerging technology [58].…”
Section: Discussionmentioning
confidence: 99%